Implikasi Etika Penyelenggara Pemilihan Umum terhadap Penegakan Demokrasi di Indonesia: Sebuah Evaluasi - Akhyaroni Fu’adah (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
This study explores the violation of the Code of Ethics by the election management body and its effect on the democratic state. As a public official, the head of the General Elections Commission (KPU) should be cautious and aware of his actions. The head of the General Elections Commission (KPU) has gotten a sanction, namely a warning sanction, strict warning sanctions, and the last strict warning sanction. However, the Election Supervisory Board (DKPP) provided the verdict for Hasyyim Ash’ari is weaker compared to the former head of KPU. This action is considered a violation of the professionality and integrity principle. This research employed the normative legal method, focusing on the analysis of the legal documents, particularly in the context of the code of ethics. The statutory approach was adopted to study laws and regulations in a comprehensive manner. The findings of this study have a significant impact on democracy enforcement, as a result. This study proposes that the DKPP Law on procedural guidelines should be revised, such as providing decision-making methods.